Optimalisasi Digital Marketing UMKM di Kelurahan Kebonsari Jember - Irawati, Tri Novita; Bulgis, Faizah Malikal; Arrufaida, Zihana; Pambudi, Aisyah Ramadhini; Haris Triyadi, Mohammad; Ayu Nugraheni, Dyah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
Many Small and Medium Enterprise (UMKM) actors nowadays are constantly popping up. But the digital world demands that people can continue to innovate and compete. As an entry sign to the revolutionary age industry 4.0 digital technology has taken a toll on UMKM's marketing of products on social media or e-commerce. With that in mind, This was the goal of a KKN group's work program in the Kebonsari district of Jember. The role of the initiative isa digitalized marketing tool for UMKM perpetrators in Kebonsari as a form of student outreach to society using data collection methods of coordination, socialization, and counseling. Students will assist in creating a social media and e-commerce account to market their products.